2007
DOI: 10.1021/jp066081o
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional and Ab Initio Study of Cr(CO)n (n = 1−6) Complexes

Abstract: Cr(CO)n (n = 1-6) systems were studied for all possible spin states using density functional and high-level ab initio methods to provide a more complete theoretical understanding of the structure of species that may form during ligand dissociation of Cr(CO)6. We carried out geometry optimizations for each system and obtained vibrational frequencies, sequential bond dissociation energies (BDE), and total CO binding energies. We also compared the performance of various DFT functionals. Generally, the ground stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
31
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 104 publications
(222 reference statements)
11
31
0
Order By: Relevance
“…The (trigonal bipyramidal) T 0 minimum of Cr(CO) 5 is found to be higher than the (square pyramidal) S 0 minimum by 0.455 eV, similarly as in recent calculations. 27 The values for the CO stretch wavenumbers are well consistent with other calculations of these vibrations. 27,28 For a quality check of the lower frequencies, we applied the calculation also to the parent compound Cr(CO) 6 and found that they agree with the experimental ones 29 within o10% (most of them within o5%).…”
Section: Calculation Of the M(co) 5 Vibrationssupporting
confidence: 88%
“…The (trigonal bipyramidal) T 0 minimum of Cr(CO) 5 is found to be higher than the (square pyramidal) S 0 minimum by 0.455 eV, similarly as in recent calculations. 27 The values for the CO stretch wavenumbers are well consistent with other calculations of these vibrations. 27,28 For a quality check of the lower frequencies, we applied the calculation also to the parent compound Cr(CO) 6 and found that they agree with the experimental ones 29 within o10% (most of them within o5%).…”
Section: Calculation Of the M(co) 5 Vibrationssupporting
confidence: 88%
“…(Table 2 and Table S14–S16 of Supporting Information). As seen from Figure 1, the structure of Sc(CO) 5 differs sharply from Ti(CO) 5 22 and Cr(CO) 5 ,13, 21, 31 both of which have a C 4v structure with four CO groups being approximately coplanar. The Sc(CO) 6 molecule has a 2 B 1 ground state with C 2v symmetry.…”
Section: Resultsmentioning
confidence: 96%
“…Yet, the more symmetric structure, that is, octahedral quartet isomer O h ( 4 A 1g ), lies 24.3 kcal/mol higher in energy. By contrast, Ti(CO) 6 , 5 V(CO) 6, 32 and Cr(CO) 6 12, 21, 31 either have a slightly distorted or perfect octahedral structures.…”
Section: Resultsmentioning
confidence: 97%
“…Density functional theory (DFT) calculations showed that the ground state of CrCO is the 7 A′ state (bent structure). The BDE calculated by using DFT is slightly higher than the experimental value . Thus, DFT appears to work well for the CrCO system.…”
Section: Introductionmentioning
confidence: 69%
“…In addition, the CO stretching vibrational frequency of CrCO in a matrix environment was also available . A large number of theoretical calculations were also performed to calculate the molecular properties of CrCO . Density functional theory (DFT) calculations showed that the ground state of CrCO is the 7 A′ state (bent structure).…”
Section: Introductionmentioning
confidence: 99%